Pemetaan Klasifikasi Iklim Schmidt-Ferguson dan Kesesuaian Agroklimat Tanaman Cabai Merah (Capsicum annuum) di Provinsi Bali - PRATAMA, GEDE SUDIKA; LANYA, INDAYATI; SARDIANA, I KETUT (Agrotrop : Journal on Agriculture Science; Vol 13 No 2 (2023)DO - 10.24843/AJoAS.2023.v13.i02.p02, 2023)
Mapping of Schmidt-Ferguson Climate Classification and Agroclimate Suitability of Red Chili Plant (Capsicum annuum) in Bali Province . Climate tends to be dynamic and changes continuously, as well as climate elements that continue to change in an area. Along with climate change and increasing rain gauge posts, the possibility of changes in climate types based on the Schmidt-Ferguson classification is inevitable. Thus, it is necessary to map the Schmidt-Ferguson climate classification in Bali Province based on data from 1991-2020 to provide an overview of the latest Schmidt-Ferguson climate classification in Bali Province. One of its uses is for the suitability criteria for agroclimatic zones for red chili (Capsicum annuum) plants. This study uses rainfall data from 1991-2020 from BMKG. This distribution data will be used to determine the Schmidt-Ferguson climate type. These results are related to the land suitability requirements for red chili (Capsicum annuum) land crops. GIS mapping will assist in zoning the Schmidt-Ferguson climate type classification area in Bali Province. The results of this study provide an overview of the latest Schmidt-Ferguson climate classification and agroclimatic suitability for red chili (Capsicum annuum) in Bali. There are significant changes when compared to the Schmidt-Ferguson climate classification for the previous period (1981-2010) with the same location and amount of data. Moreover, red chili (Capsicum annuum) plants are generally able to grow throughout the province of Bali, where the most suitable areas are in the northern coastal area.